How valid is the determination of hematocrit values to detect blood manipulations? - Schmidt, W.; Biermann, B; Winchenbach, P.; Lison, S.; Boning, D. (International Journal of Sports Medicine, 2000)
The aim of this paper is a critical reflection of the practice in competitive cycling to use the hematocrit value (Hct) as an indirect control measure for doping with erythropoietin. To demonstrate the individual physiological variation of Hct values, five different studies were performed: 1) Eight subjects were observed (i) during 23 h after a 1 h lasting bout of cycle exercise at 60% of maximum performance and (ii) during 24h under control conditions. 2) Seven subjects were exposed to a 20 min period of -7 head down tilt (HDT), which was followed by 15 min in sitting position. 3) From four subjects blood samples were taken in a sitting position up to 60 min after they had ingested 1 liter isotonic saline solution. 4) Ten subjects performed a vita maxima test on a cycle ergometer, starting at 100W and increasing the workload by 17W every minute. 5) Four elite cyclists participated in a 10 days competition (1,700 km). RESULTS: 1) During the 24h observation period Hct decreased during the night from 45.3+/-3.1 % to 42.9+/-1.5% and returned to the initial values in the morning. This diurnal variation was even more pronounced after submaximal exercise (-4.1 %). 2) Due to fluid shifts from the interstitial into the intravasal compartment, HDT was accompanied by a 3.1+/-0.5% lower Hct. 3) Drinking of the isotonic saline solution also reduced the hematocrit by 3.3+/-0.5% after one hour. 4) Maximum cycle exercise increased the Hct from 46.8+/-2.4 % to 51.3+/-1.9% which was due to a 15 % decrease in plasma volume. 5) Repeated bouts of cycle-exercise reduced the Hct from 46.4+/-1.5% to 41.3+/-1.6%. CONCLUSIONS: All experiments demonstrate that the Hct is not a constant value but can be considerably changed by physiological measures. Clinical studies show that brain oxygen supply decreases with increasing Hct-values, which are also associated with a higher risk of stroke accidents. We therefore recommend to use a Hct-limit solely under strongly controlled standardized conditions to protect professional cyclists from hazardous manoeuvre until more appropriate methods to detect EPO-doping are developed.